(untitled) (Práxis Educativa, 2025)
This article presents the results of a study with young university students enrolled in the Free University Program (PUG, acronym in Portuguese). The purpose of the research was to identify the students’ profile and to understand how their lived realities influence either the continuation or the abandonment of their studies. Based on Zygmunt Bauman’s sociological theory, the empirical research was conducted with students from a community university in southern Brazil – the Universidade do Oeste de Santa Catarina (UNOESC). Data were obtained from the Secretariat of Education of Santa Catarina and from the Student Support Service of UNOESC – Joaçaba campus. The study highlights, among other findings, that the academic trajectories of these young people are not linear. Their permanence at the university is constantly threatened by instability and the uncertainties of everyday life. Keywords: Higher Education. Young university students. Free University Program. Zygmunt Bauman.